Calling for "The new cultural normal": Learning from intra-company biculturalism - Lisa Tran; Bartjan Pennink (The Central European Review of Economics and Management (CEREM), 2022)
Aim: This research aims to understand the value of individuals having several inherent cultures and explore their specific needs and skills to improve managing cultural challenges in the work environment. The emerging conceptual framework of reaching "The New Cultural Normal" demonstrates opportunities for dealing with cross-cultural situations not only internationally but especially intra-national. Design / Research methods: Based on insights and narratives of bicultural employees collected through 18 interviews, several vital categories emerged followed by the attribution of each to a corporate setting and considering which has the most substantial influence on that category. As biculturalism is an extreme form of coping with cultural diversity, the interviewees represent vital experts in coping with culturally diverse challenges. Conclusion / Findings: The emerging concept of reaching 'The New Cultural Normal' describes the process of attaining the status of full integration of biculturalism among organizations. It will help each corporate setting level, defined as bicultural employees, colleagues, supervisors, and the company, to enhance their awareness of dealing with cross-cultural situations. Originality / value of the article: This study provides a beneficial starting tool for shaping the future workplace where more inclusion and contentment will lead to qualitative improved team outcomes thus increasing corporate performance and can even result in long-term societal changes.
Keywords: M14; M16; 330; Cultural Diversity; Biculturalism; Intra-national; Cross-cultural Management; Work Place Integration; Organization